2010
DOI: 10.1007/s12206-010-0416-2
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial effect on thermal conductivity of diamond-like carbon films

Abstract: Diamond-like carbon (DLC) has been of interest as a promising coating for protection and insulating layer in micro-electromechanical systems due to high hardness, wear resistance, transparency in IR range, chemical inertness and biocompatibility. The interfacial effect on thermal transport is studied for DLC films deposited on Al 2 O 3 substrates with an ion gun method. Thermal conductivity of DLC thin films is measured with a 3ω method. DLC films show the thickness-dependent thermal conductivity, which is und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…These factors make the coatings promising for use in, among others, machine components and cutting tools. Of interest in this study is, however, the low thermal conductivity (in the range of 1-3 W/mK) that has been measured for these thin coatings [20,26,4].…”
Section: Introductionmentioning
confidence: 99%
“…These factors make the coatings promising for use in, among others, machine components and cutting tools. Of interest in this study is, however, the low thermal conductivity (in the range of 1-3 W/mK) that has been measured for these thin coatings [20,26,4].…”
Section: Introductionmentioning
confidence: 99%
“…It was thus hypothesized that this, in turn, affects a higher surface-temperature increase, and thus a larger viscosity decrease for a negative SRR than for a positive SRR, where the heat partitioning between the isolating disc and the steel ball is 50:50 [30]. This case is especially relevant for the current study since the reported heat conductivity of the glass was 1.5 J/mK, which is almost the same as a typical DLC coating [31][32][33]. Moreover, a similar hypothesis on the thermal aspects and a reduction of the viscosity, and consequently, a friction reduction due to the DLC isolating effect was also suggested recently by Björling et al [17] for EHL contacts.…”
Section: Discussionmentioning
confidence: 99%
“…A chromium-based interlayer with a thickness of 0.1-0.3 lm deposited by magnetron sputtering was used to improve the adhesion. The thermal conductivities were not measured on these specific coatings, but approximated by the formula obtained by Kim et al [31] that is expressed in Fig. 1.…”
Section: Test Specimens and Lubricantmentioning
confidence: 99%
“…However, the present authors have presented an investigation in which friction reduction with DLC coatings was measured [7] in full film EHL even when the combined RMS roughness of the surfaces was in the range of 155-355 nm. Based on a simplified analytical estimation of the temperature increase in the lubricant film induced by DLC surface coating, the authors proposed that the friction reduction could be a result of thermal insulation due to the low thermal conductivity observed for some DLC coatings [2,31,40]. The temperature increase in the lubricant film would reduce the viscosity and thereby reduce the coefficient of friction.…”
Section: Introductionmentioning
confidence: 99%